Research on Capacity Optimization Configuration of Wind-solar-storage-load Micro-grid System Based on Energy Router - ZHANG Jietian; LI Chi (Kongzhi Yu Xinxi Jishu)
Capacity configuration of hybrid wind-solar-storage-load micro-grid system is a key issue in the construction of energy internet. Through reasonable capacity configuration, the overall loss of power electronic converter in micro-grid system can be reduced. In order to realize energy saving of the whole system, it is necessary to accurately model the loss characteristics of the micro-grid system at first. Compared with the traditional modeling method in which converter efficiency is regarded as a fixed value, this paper used the piecewise linear method to describe the variation characteristics of the converter efficiency of the micro-grid system more accurately with the output power. In addition, the micro-grid system established in this paper comprehensively considered the complementary characteristics of wind energy and solar energy, as well as the energy storage characteristics of the centralized electric vehicle charging station, to improve the flexibility and reliability of the system configuration. Based on the above micro-grid system model, the optimal energy storage configuration of wind power system and solar power system and system is realized by simulated annealing algorithm, and the accuracy and effectiveness of the proposed are verified by a case study. Compared with the general expert configuration, this optimized configuration can reduce the loss by 36.68%. When the electric vehicle is used as an energy storage device, compared with the case where the electric vehicle is only used as a load, the overall loss of the micro-grid system can be reduced by 9.30%.